Molecular basis of mRNA transport by a kinesin-1-atypical tropomyosin complex - Dimitrova-Paternoga, Lyudmila Nikolova; Jagtap, Pravin Kumar Ankush; Cyrklaff, Anna; Vaishali; Lapouge, Karine; Sehr, Peter; Perez, Kathryn; Heber, Simone; Löw, Christian; Hennig, Janosch; Ephrussi, Anne (Genes & development, 2021)
Kinesin-1 carries cargos including proteins, RNAs, vesicles, and pathogens over long distances within cells. The mechanochemical cycle of kinesins is well described, but how they establish cargo specificity is not fully understood. Transport of oskar mRNA to the posterior pole of the Drosophila oocyte is mediated by Drosophila kinesin-1, also called kinesin heavy chain (Khc), and a putative cargo adaptor, the atypical tropomyosin, aTm1. How the proteins cooperate in mRNA transport is unknown. Here, we present the high-resolution crystal structure of a Khc-aTm1 complex. The proteins form a tripartite coiled coil comprising two in-register Khc chains and one aTm1 chain, in antiparallel orientation. We show that aTm1 binds to an evolutionarily conserved cargo binding site on Khc, and mutational analysis confirms the importance of this interaction for mRNA transport in vivo. Furthermore, we demonstrate that Khc binds RNA directly and that it does so via its alternative cargo binding domain, which forms a positively charged joint surface with aTm1, as well as through its adjacent auxiliary microtubule binding domain. Finally, we show that aTm1 plays a stabilizing role in the interaction of Khc with RNA, which distinguishes aTm1 from classical motor adaptors.